IL‐22 in tissue‐protective therapy. (27th May 2013) - Mühl, Heiko; Scheiermann, Patrick; Bachmann, Malte; Härdle, Lorena; Heinrichs, Anika; Pfeilschifter, Josef
<x xml:space="preserve">Abstract</x> IL‐22, a member of the IL‐10 cytokine family, has recently gained significant attention as a protective agent in murine models of diseases driven by epithelial injury. Like its biochemical and functional sibling IL‐10, IL‐22 elicits cellular activation primarily by engaging the STAT3 signalling pathway. Exclusively produced by leukocytes, but targeting mostly cells of epithelial origin, IL‐22 has been proposed as a specialized cytokine messenger acting between leukocytic and non‐leukocytic cell compartments. A lack of response in leukocytes to IL‐22 mirrors tightly controlled IL‐22 receptor expression and probably explains the apparent lack of instant adverse effects after systemic IL‐22 administration to mice. Anti‐apoptotic, pro‐proliferative and pro‐regenerative characteristics the major biological properties of this cytokine. Specifically, application of IL‐22 is associated with tissue protection and/or regeneration in murine models of infection/microbe‐driven inflammation at host/environment interfaces, ventilator‐induced lung injury, pancreatitis and liver damage. Overall, preclinical studies would support therapeutic administration of seemingly well‐tolerated recombinant IL‐22 for treatment of an array of acute diseases manifested in epithelial tissues. However, the feasibility of prolonged administration of this cytokine is expected to be restricted by the tumourigenic potential of the IL‐22/STAT3 axis. IL‐22, moreover, apparently displays an inherent context‐specific capacity to amplify distinct aspects of autoimmune inflammation. Here, the prospects, expectations and restrictions of IL‐22 administration in tissue‐protective therapy are discussed.